2022
DOI: 10.3390/plants11212882
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Supplementation Alleviates Adverse Effects of Ammonium on Ssamchoo Grown in Home Cultivation System

Abstract: Ssamchoo is recently attracting attention as a household hydroponic vegetable in Korea. It has a refreshing texture and a rich content of vitamins and fiber. Ssamchoo with a wide leaf area is suitable for traditional ssam or vegetable wraps, as well as a vegetable for salads; thus, it can be used in a variety of dishes. However, Ssamchoo plants responds sensitively to the nutrient solution, and it is often difficult to secure sufficient leaf area and robust growth using a commercial nutrient solution for leafy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Increased shoot fresh weight, chlorophyll content, leaf area, vitamin C, and antioxidant enzyme activities [108] 10. Conclusions and Future Perspectives Ammonium assimilation into plant metabolites requires limited energy than nitrate assimilation, as it is already in reduced form.…”
Section: Eucalyptus Urophylla X Eucalyptus Grandismentioning
confidence: 99%
“…Increased shoot fresh weight, chlorophyll content, leaf area, vitamin C, and antioxidant enzyme activities [108] 10. Conclusions and Future Perspectives Ammonium assimilation into plant metabolites requires limited energy than nitrate assimilation, as it is already in reduced form.…”
Section: Eucalyptus Urophylla X Eucalyptus Grandismentioning
confidence: 99%
“…Ssamchoo) is a vegetable commonly used in Ssam, a Korean specialty food. However, cultivating Ssamchoo hydroponically poses challenges due to its sensitivity to the composition and concentration of the nutrient solution (Noh and Jeong, 2022). A research reported that nutrient solution (the ratio of NO 3 − to NH 4 + to urea is 50: 25: 25) combined with silicon (10.7 mmol L −1 ) is suitable for planting Ssamchoo in a household hydroponic system.…”
Section: Hydroponic Technologiesmentioning
confidence: 99%
“…A research reported that nutrient solution (the ratio of NO 3 − to NH 4 + to urea is 50: 25: 25) combined with silicon (10.7 mmol L −1 ) is suitable for planting Ssamchoo in a household hydroponic system. This optimized nutrient solution not only allows for achieving the highest yield but also effectively mitigates the harmful effects of ammonium on Ssamchoo (Noh and Jeong, 2022).…”
Section: Hydroponic Technologiesmentioning
confidence: 99%